Design of a bulk acoustic resonator - Zhang, Haozhe (2019)
Bandpass filter is one of the key components in the data communication system, which is used to transmit or receive signals at a certain frequency within a certain bandwidth. There are mainly three types of bandpass filters for wireless data communication applications. In this work, the 3 types of filters are briefly introduced: the ceramic filters, the surface acoustic wave (SAW) type filters, and the bulk acoustic wave (BAW) type The filters all have a small loss, however, in the same volume, BAW has the highest Q factor value among all 3 kinds of filters and it shows great performance for high frequencies, thus demonstrating great potential in the RF applications. This report introduces one approach to build the BAW resonator model. And based on the model, device performance is optimized by tuning some parameters such as the thickness of the piezoelectric layer materials of the active piezoelectric layer and different structure s of the resonator.